2015
DOI: 10.3389/fmicb.2015.00652
|View full text |Cite
|
Sign up to set email alerts
|

High pressure thermal inactivation of Clostridium botulinum type E endospores – kinetic modeling and mechanistic insights

Abstract: Cold-tolerant, neurotoxigenic, endospore forming Clostridium (C.) botulinum type E belongs to the non-proteolytic physiological C. botulinum group II, is primarily associated with aquatic environments, and presents a safety risk for seafood. High pressure thermal (HPT) processing exploiting the synergistic effect of pressure and temperature can be used to inactivate bacterial endospores. We investigated the inactivation of C. botulinum type E spores by (near) isothermal HPT treatments at 300–1200 MPa at 30–75°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 90 publications
1
19
0
Order By: Relevance
“…In particular, HPs of Ͼ500 MPa in conjunction with elevated temperatures (T Ͼ 90°C, and with compression heating generating T Ϸ 121°C) have commercial potential for the preservation of low-acid, shelfstable, high-value foods (6,7). Research in recent years on how HP at elevated temperatures results in spore killing, primarily on spores of various Bacillus species, has indicated that HP generally kills spores by triggering spore germination (8)(9)(10)(11)(12), and the elevated temperatures can now kill the heat-sensitive germinated spores (6, 7, 10 -12).…”
mentioning
confidence: 99%
“…In particular, HPs of Ͼ500 MPa in conjunction with elevated temperatures (T Ͼ 90°C, and with compression heating generating T Ϸ 121°C) have commercial potential for the preservation of low-acid, shelfstable, high-value foods (6,7). Research in recent years on how HP at elevated temperatures results in spore killing, primarily on spores of various Bacillus species, has indicated that HP generally kills spores by triggering spore germination (8)(9)(10)(11)(12), and the elevated temperatures can now kill the heat-sensitive germinated spores (6, 7, 10 -12).…”
mentioning
confidence: 99%
“…On the other hand, Paidhungat and others (), Margosch and others (), and Reineke and others () proposed a 2‐step kinetic model, with stage I the partial spore germination and stage II the spore inactivation by a combination of pressure and temperature due to higher stress sensitivity. More recently, a different inactivation mechanism was observed by Lenz and others () for C. botulinum spores, since 1st‐order kinetics was verified in this case. Therefore, more work should be done to better understand the inactivation mechanisms of spores by PATS.…”
Section: Novel Sterilization Technologiesmentioning
confidence: 47%
“…Researches always focused on the spores of B. cereus which were more heat‐resistant (Evelyn & Silva, ; Gaillard, Leguerinel, & Mafart, ; Lenz, Reineke, Knorr, & Vogel, ) while less work aimed at the inactivation of the vegetative cells (Cronin & Wilkinson, ). What's more, the exact mechanism about the thermal inactivation remained unclear (Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the food industry, the bacterial membrane is known to be a primary target for the inactivation treatments which is applied during processing to guarantee food safety. Propidium iodide (PI) is a nucleic acid dye penetrates only cells with damaged membranes, so it can be an indication of the membrane integrity, while car- Researches always focused on the spores of B. cereus which were more heat-resistant (Evelyn & Silva, 2016;Gaillard, Leguerinel, & Mafart, 1998;Lenz, Reineke, Knorr, & Vogel, 2015) while less work aimed at the inactivation of the vegetative cells (Cronin & Wilkinson, 2008b). What's more, the exact mechanism about the thermal inactivation remained unclear (Wang et al, 2017) standard NB media contains 0.5% NaCl; Peptone, Beef extract powder; pH: 7.2 AE 0.2) for all experiments.…”
Section: Introductionmentioning
confidence: 99%